Development of a Powder Formulation for Effective Removal of Toxic Chemicals from Textile Materials - P. N. Kolesnikov; V. P. Khantov (Вестник войск РХБ защиты, 2023)
The article is dedicated to the development of a powder formulation for the decontamination of textile materials. The degassing effect is achieved due to the capillary effect, created by the nanoparticles, included in the above mentioned formulation, that penetrate into the pores of the fibres of the textile material. The degassing formulation contains (weight) А12О3 12 % и SiO2 88 %, with polydisperse microparticles 85 % (weight) and nanoparticles 15 % (weight). The necessary completeness of the decontamination is achieved after the removal of more than (30±7) % of the liquid phase of toxic chemicals. This result may be achieved after the use of powder formulations with particles with an average size of less than 50 µm. The elaborated powder formulation allows to remove more than 80 % of the liquid phase of toxic chemical, that provides the necessary completeness of the decontamination of military equipage.